Exploring the Views of Mosque Committee Members on Mosque Religious Education Programs in Gombak - Shukran Abdul Rahman; Lihanna Borhan; Majdan Alias; Mohd Noh Abdul Jalil; Khamsiah Ismail; Che Razi Jusoh; Aliza Elias; Mohd Helmi Mohd Sobri; Muhammad Ayman Al-Akiti; Sofiah Shamsudin; Che Mahzan Ahmad; Kamaruzzaman Abdul Manan (Millah: Journal of Religious Studies, 2021)
There are a multitude of social problems characterised by the growth of crime rate of violence, religious disintegration, hatred, religious disunity and tension. Such problems have raised serious attention from various parties as they lead to social disintegration and will eventually harm social security as a whole. The phenomena could be attributed to the lack of religious understanding; a critical factor in constructing the moral behaviour of human beings. A study has been conducted to obtain feedback from mosque committee members on the nature of mosque religious education curriculum. Focus Group Discussions had been conducted by engaging relevant stakeholders of mosques in order to identify the views of mosque committee members on the mosque religious education curriculum in the district of Gombak, a district in the state of Selangor, Malaysia. The findings have been analysed using thematic analysis. The findings show that mosque committee members highlighted several issues which concern mosque religious education structure, education resource, participants content of curriculum, teaching and learning approaches and their expected outcomes. The findings increase the understanding on the roles of mosque as centre to acquire knowledge for sustainable development. The information can be used as bases for the development of Mosque Religious Education Curriculum.